Nursing Students' Perceived Learning Outcomes, Motivation to Learn and Grade Achieved in a Digital Blended Learning Course: A Norwegian Cross-Sectional Study - Christine Tørris; Mona Elisabeth Meyer; Ida Hellum Sandbekken; Hedvig Halvorsrud; Marianne Molin (MDPI AG, 2022)
The COVID-19 pandemic forced educational institutions to move online, and it is important to understand how students perceive learning in a digital learning environment. We aimed to investigate students' perceived learning outcomes in a digital learning environment and associations between perceived learning outcomes and grades achieved. An anonymous electronic survey was used (n = 230, response rate 34%). A significant linear relationship between overall perceived learning outcome and grade achieved was found (B 0.644, 95% CI 0.52 to 0.77). Of the different learning activities, attending digital seminars were positively associated with grades (B 0.163, 95% CI 0.002 to 0.32). In particular, participating in voluntary colloquium group (B 0.144, 95% CI 0.03 to 0.26) and motivation to learn (B 0.265, 95% CI 0.13 to 0.41) predicted the students' grades. Intrinsic motivation was positively associated with grades (B 0.285, 95% CI 0.12 to 0.45), and extrinsic motivation was negatively associated with grades (B-0.213, 95% CI-0.35 to -0.07). Nursing students' perceived learning outcomes and grades were positively associated. Of the different learning activities, attending digital seminars predicted higher grades. Additionally, attending colloquium groups and being motivated to learn predicted higher grades, while high extrinsic motivation was associated with lower grades.